The ACCENT-VOCBAS field campaign on biosphere-atmosphere interactions in a Mediterranean ecosystem of Castelporziano (Rome): site characteristics, climatic and meteorological conditions, and eco-physiology of vegetation (Biogeosciences, 2009)
Biosphere-atmosphere interactions were investigated on a sandy dune Mediterranean ecosystem in a ﬁeld campaign held in 2007 within the frame of the European Projects ACCENT and VOCBAS. The campaign was carried out in the Presidential estate of Castelporziano, a periurban park close to Rome. Former campaigns (e.g. BEMA) performed in Castelporziano investigated the emission of biogenic volatile organic compounds (BVOC). These campaigns focused on pseudosteppe and evergreen oak groves whereas the contribution of the largely biodiverse dune vegetation, a prominent component of the Mediterranean ecosystem, was overlooked. While speciﬁc aspects of the campaign will be discussed in companion papers, the general climatic and physiological aspects are presented here, together with information regarding BVOC emission from the most common plant species of the dune ecosystem. During the campaign regular air movements were observed, dominated by moderate nocturnal land breeze and diurnal sea breeze. A regular daily increase of ozone concentration in the air was also observed, but daily peaks of ozone were lower than those measured in summer on the same site. The site was ideal as a natural photochemical reactor to observe reaction, transport and deposition processes occurring in the Mediterranean basin, since the sea-land breeze circulation allowed a strong mixing between biogenic and anthropogenic emissions and secondary pollutants. Measurements were run in May, when plant physiological conditions were optimal, in absence of severe drought and heat stress. Foliar rates of photosynthesis and transpiration were as high as generally recorded in unstressed Mediterranean sclerophyllous plants. Most of the plant species emitted high level of monoterpenes, despite measurements being made in a period in which emissions of volatile isoprenoids could be restrained by developmental and environmental factors, such as leaf age and relatively low air temperature. Emission of isoprene was generally low. Accounting for the high monoterpene spring emission of the dune ecosystem may be important to correct algorithms at regional and ecosystem levels, and to interpret measurements of ﬂuxes of volatile isoprenoids and secondary pollutants.

Measuring, modelling and testing ozone exposure, flux and effects on vegetation in southern European conditions--what does not work? A review from Italy. (Environmental pollution (Barking, Essex : 1987), 2007)
Ozone (O3) exposure at Italian background sites exceeds UN/ECE concentration-based critical levels (CLe(c)), if expressed in terms of AOT40. Yet the occurrence of adverse effects of O3 on forests and crops is controversial. Possible reasons include (i) ability of response indicators to provide an unbiased estimate of O3 effects, (ii) setting of current CLe(c) in terms of cut-off value and accumulation level, (iii) response functions adopted to infer a critical level, (iv) environmental limitation to O3 uptake and (v) inherent characteristics of Mediterranean vegetation. In particular, the two latter points suggest that critical levels based on accumulated stomatal flux (CLe(f)) can be a better predictor of O3 risk than CLe(c). While this concept is largely acknowledged, a number of factors may limit its applicability for routine monitoring. This paper reviews levels, uptake and vegetation response to O3 in Italy over recent years to discuss value, uncertainty and feasibility of different approaches to risk assessment.

Monitoring tropospheric ozone impact on plants in natural and urban areas with a Mediterranean climate (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2005)
Abstract To investigate the real linkage and effectiveness of using the AOT40 index and ozone stomatal flux (FO3) in the assessment of physiological alteration/leaf injury on clover clones sensitive to ozone and Quercus ilex plants, two statistical techniques ? Partial Least Squares (PLS) and Neural Net Analysis (NNA) ? were applied. Different results were obtained in relation to the statistical method chosen. Linear methodologies applied to clover highlighted the role of temperature (TEMP) and O3 concentration (O3Mean) in affecting photosynthesis (PHOTO), leaf injury, and stomatal conductance (COND). In Quercus plants, COND was linearly correlated to two environmental variables, TEMP and Vapour Pressure Deficit (VPD), and to two physiological variables, PHOTO and Leaf Transpiration (TRASP), whereas PHOTO was correlated with TEMP, sO3, COND and sub-stomatal CO2/external CO2 ratio (Ci/Ca). These linear relationships were, in part, modified by NNA. In fact, non-linear relationships between environmental variables, and morphological and physiological variables were evident, suggesting caution when risk assessments are made on ozone concentration-based critical levels. Both plant types showed a relationship with FO3 that negatively affected leaf injury and PHOTO in clover and Quercus plants, respectively, suggesting that ozone flux-based critical levels were more effective in linking with leaf injuries or reduction in carbon metabolism.
doi: 10.1080/11263500500333966

Ozone uptake by an evergreen Mediterranean Forest () in Italy. Part I: Micrometeorological flux measurements and flux partitioning (Atmospheric Environment, 2005)
Ozone, water and energy ﬂuxes have been measured over a Mediterranean evergreen forest in Central Italy from August to October 2003 with the eddy-correlation technique in order to evaluate the amount of ozone taken up by plants in dry summer and in mild autumn conditions. The stomatal ozone ﬂuxes have been calculated using the analogy with water vapor ﬂuxes inside the stomata, which are easily measurable. The total ozone dose was obtained by integrating the stomatal ﬂuxes over time. Stomatal ﬂux resulted a minor part (31.5%) of the total ozone ﬂux over the forest ecosystem. The main part of ozone deposition follows non-stomatal pathways. Chemical sink seems to play a relevant role in the morning non-stomatal deposition. Stomatal uptake is enhanced by water availability but, on the average, it does not exceed the 34.4% of the total ozone ﬂux. A comparison between the cumulated stomatal ozone ﬂuxes and the currently used AOT40 exposure index highlighted important distortions introduced by this index. AOT40, which do not take into account plant physiology, lead to substantial overestimation of ozone risk, particularly when water supply is limited, as occurs frequently in Southern European and Mediterranean areas.

Gas exchange measurements and an indirect estimate of primary production in a holm-oak ecosystem (FRESENIUS ENVIRONMENTAL BULLETIN, 1998)
An original and simple primary production model is presented. Annual trends of the daily average values of net photosynthesis and leaf transpiration for helm oak are showed. Moreover, primary production data were obtained. To validate the model, an evaluation between estimated results and field measurements was performed, obtaining a strong correspondence.
Citation

O3 AND 03+C02 EFFECTS ON A MEDITERRANEAN EVERGREEN BROADLEAF TREE, HOLM OAK (QUERCUS iLEX L.) (Chemosphere, 1998)
The aim of this work is to analyze the effects of a) short-term treatments with different concentrations of 0, (daily 6-hour fumigation with 0, 65, 175 and 300 ppb for 3-4 days); and 6) a medium term treatment with O9 (150 ppb three times a week for thirty days on the whole) and CO2 (700 ppm) on gas exchange, chlorophyll fluorescence, and peroxidase activity in holm oak (Quercus ilex L.) leaves. The results show that net photosynthesis, transpiration, Fv/Frvr ratio and POD activity were not influenced until an O1 concentration of 300 ppb was reached. At this threshold, significant alterations in these physiological and biochemical parameters were found. The treatment with +C02 +O, showed an increase of net photosynthesis suggesting thus an antagonistic effect of CO2 with regard to Oj-induced injuries, while CO2 alone increased photosynthesis and decreased transpiration but induced no effects on FV/‘F, ratio or peroxidase activity. From our data, holm oak shows a resistance to episodes ofphotochemical 0, stress, that in the Mediterranean region can reach peaks of > 100 ppb. This response is likely to be due to the morpho-anatomic structure of helm oak leaves and their sclerophyllous adaptations. This might leads helm oak to adopt a stress tolerance strategy with regard to leaf response to O,, the effects of which cannot be ameliorated by an increase of atmospheric CO2